The poetics of late Latin literature - Elsner, Jaś; Elsner, Jaś; Hernández Lobato, Jesús; Hernández Lobato, Jesús (Oxford studies in late antiquity, 2017)
For a host of reasons, traditionalist scholarship has failed to give a full and positive account of the formal, aesthetic and religious transformations of ancient poetics in late antiquity. This collection of new essays attempts to capture the vibrancy of the living ancient tradition reinventing itself in a new context in the hands of a series of great Latin writers of the fourth and fifth centuries AD